Physical properties of hydrothermally treated rubberwood [Hevea brasiliensis (Willd. ex A. Juss.) Müll. Arg.] in different buffered media - Ali, Md. Rowson; Abdullah, Ummi Hani; Ashaari, Zaidon; Hua, Lee Seng; Hamid, Norul Hisham; Kamarudin, Siti Hasnah (MDPI, 2022)
The dimensional instability of rubberwood [Hevea brasiliensis (Willd. ex A. Juss.) Müll. Arg.] is one of the major drawbacks that limits its utilization. Therefore, treatment is needed to improve these properties. Hydrothermal treatment in different buffered media is one of the techniques that improve its dimensional stability. The physical properties of hydrothermally treated rubberwood in different buffered media (pH 4, 6, 8, 10) and tap water (pH 7.43) with different temperatures (160 °C, 180 °C and 200 °C) were studied. In this study, physical properties such as equilibrium moisture content (EMC), density (ρ), mass loss (ML), water absorption (WA), volumetric swelling coefficient (VSC), thickness swelling (TS) and anti-swelling efficiency (ASE) were investigated for both treated and untreated specimens. Both the buffered media and temperature significantly affected the physical properties. The results indicated that the EMC (%), ρ (kg/m3), ML (%), VSC (%), TS (%) of treated rubberwood samples reduced as the treatment temperature increased. With the exception of WA (%), as WA increased when the treatment temperature increased from 160 °C to 180 °C but started to decrease when the temperature was further increased to 200 °C. The research study also exhibited that hydrothermal treatment using buffered media at different temperatures enhanced the dimensional stability of the treated samples. Alkaline media gave the best results on the physical properties compared to other treatment medias.